Exploring the Influence of Different Saccharomyces cerevisiae Strains and Hop Varieties on Beer Composition and Sensory Profiles - Antonella Costantini; Maurizio Petrozziello; Christos Tsolakis; Andriani Asproudi; Enrico Vaudano; Laura Pulcini; Federica Bonello; Katya Carbone; Maria Carla Cravero (Foods, 2025)
The influence of different Saccharomyces cerevisiae (Sc) strains and hop varieties on the physical, chemical and sensory properties of beer was investigated. ISE77, an oenological Sc strain screened for the IRC7 gene and β-lyase activity, and a commercial yeast, as a control, were experimented with two hops (dry hopping), Mosaic® (M) and Hallertau Mittelfrüh (HM). Both hop variety and yeast strain exerted a considerable influence on the organoleptic profile of the beer. Samples with M hops exhibited elevated levels of specific volatile compounds (e.g., limonene and linalool). ISE77 generated higher levels of esters, irrespective of the hop variety employed, imparting fruity and floral characteristics. Moreover, the beers fermented with ISE77 showed herbal and spicy notes. Regardless of the hop variety, samples brewed with the control yeast showed higher honey and caramel note levels. Beers fermented with ISE77 and HM exhibited remarkable similarities to those produced with ISE77 and M, particularly for some odour attributes (citrus, exotic fruits, and aromatic herbs). These attributes were more intense than in beers fermented with the control yeast and HM. This study demonstrated the potential of oenological Sc strains to achieve innovative brewing outcomes when combined with selected hops.